2003
DOI: 10.1590/s0041-87812003000300006
|View full text |Cite
|
Sign up to set email alerts
|

Dura mater mitral and tricuspid bioprostheses: 30 years of follow-up

Abstract: The dura mater bioprosthesis played an important role in the treatment of patients with mitral and tricuspid valve disease. The low rate of thromboembolism and the long period of follow-up without evidence of valve dysfunction, which occurred for several of our patients, are important characteristics of these bioprosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a period of more than 30 years at the Mayo Clinic, 333 surgical patients received biological prostheses and 45 received mechanical prostheses for surgical treatment of Ebstein Anomaly and, a comparative study concluded that the presence of a bioprosthesis is an independent predictor of increased survival [12]. Puig et al reported three patients with tricuspid insufficiency who underwent valve replacement with homologous dura mater cardiac bioprostheses glycerol-preserved (Two patients were well 28 and 27 years later, and the third was lost to follow-up after 20 years) [13,14]. These reports strongly suggest the good results of isolated tricuspid valve bioprosthesis.…”
Section: Fig 1 -1) Transesophageal Echodopplercardiogram Showing Promentioning
confidence: 99%
“…In a period of more than 30 years at the Mayo Clinic, 333 surgical patients received biological prostheses and 45 received mechanical prostheses for surgical treatment of Ebstein Anomaly and, a comparative study concluded that the presence of a bioprosthesis is an independent predictor of increased survival [12]. Puig et al reported three patients with tricuspid insufficiency who underwent valve replacement with homologous dura mater cardiac bioprostheses glycerol-preserved (Two patients were well 28 and 27 years later, and the third was lost to follow-up after 20 years) [13,14]. These reports strongly suggest the good results of isolated tricuspid valve bioprosthesis.…”
Section: Fig 1 -1) Transesophageal Echodopplercardiogram Showing Promentioning
confidence: 99%
“…When use of dura mater valves was discontinued, 3000 patients had gotten this implant, and results were very good when compared to other available valves (6).…”
mentioning
confidence: 99%